MUTU ORGANOLEPTIK DAN KIMIA PETIS UDANG REBON (Mysis relicta) DENGAN PENAMBAHAN GARAM DAN LAMA PEMASAKAN BERBEDA - Dahlia Dahlia; Suparmi Suparmi; Desmelati Desmelati; Santhy Wisuda Sidauruk (Berkala Perikanan Terubuk, 2021)
Shrimp paste is a source of protein because the protein of shrimp paste has a high protein (15-20 g/100 g). However, shrimp paste is only consumed as a flavor and seasoning mixture. The study was aimed to determine the quality of organoleptic and chemical of shrimp paste using the difference of salt and cooking time. The used method was an experimental method with a factorial Completely Randomized Design (CRD) consisting of 3 treatments, namely A1 (10 g salt), A2 (15 g salt) and A3 (20 g salt). Meanwhile, cooking time was 30 minutes, 45 minutes, and 60 minutes. The tested parameters were organoleptic (flavor, odor, texture, and appearance), proximate (moisture, ash, protein, and fat), and pH. The results showed that the interaction between 15 g salt and 45 minutes of cooking time was the best treatment with the organoleptic of 7.29 flavor (shrimp taste slightly reduced, less salty), 7.59 odor (the specific odor of shrimp paste), 7.21 texture (thick, homogenous, soft), 7.63 appearance (blackish brown). The proximate of shrimp paste was 38.12% moisture, 3.05% ash, 9.68% protein, 0.72% fat, and 7.05 pH.